Bavinck's Theological Identity Regarding A Recent Criticism Of The Two Bavincks Hypothesis - Choi, Changjun (STT Reformed Injili Internasional, 2021)
The present article handles the recent criticism of the so-called ‘two Bavincks hypothesis’ of Jan Veenhof voiced by Bavinck scholars. Since 1968 Veenhof has introduced the two Bavincks hypothesis, this hypothesis has had significant effects on Bavinck studies in the second half of the twentieth century. Following Veenhof’s bipolar portrayal of Bavinck, several Bavinck scholars have labeled Bavinck’s theological characteristic as the two Bavincks, namely, advocating his theological identity as a figure who has unresolved duality between orthodoxy and modernity in his thought. However, numerous studies have recently attempted to amend and redress this two Bavincks hypothesis by scholars who only argue for one Bavinck rather than two Bavincks. In the light of this, the present article first examines the recent criticisms for the two Bavincks hypothesis respectively and further argues that there is one Bavinck, who is an orthodox Calvinist and at the same time a modern European man.